CUESTIONARIO PARA EL ENCUESTADOR - Coronell, Daniel (La Sociología en sus Escenarios, 2009)
Abstract. It has called the attention, among other things, that weeks ago wrote in the Time, this explanation on the increasing numbers of unemployment: “If one at great length watches the tendencies that the Dane reports from 2002 to today, one concludes that the population that is not interested in working it has come growing slowly… The increase of the unemployment is not meaning that the homes are becoming impoverished or that are going to them worse”. Resumen. Ha llamado la atención, entre otras cosas, que hace unas semanas escribiera en El Tiempo, esta explicación sobre las crecientes cifras de desempleo: "Si uno mira detenidamente las tendencias que reporta el Dane desde 2002 hasta hoy, se concluye que la población que no está interesada en trabajar ha venido creciendo lentamente... El aumento del desempleo no está significando que los hogares se estén empobreciendo o que les esté yendo peor".